Financial Risks in the Aluminum Industry: A Brief Review - Arzu Safarli; Novruz Aslanov (Research Reviews, 2024)
The assessment of potential financial risks within the globally strategic aluminum industry holds significant importance. The research comprehensively analyzed the general financial risks associated with the aluminum sector from various perspectives, considering factors such as price fluctuation, accessibility of raw materials, sustainability considerations, and technological advancements as primary directional criteria. The findings of the study elucidated key requirements aimed at ensuring the financial stability of the aluminum industry within the analyzed context.